Costi dei figli, valore dei figli. Economia e cultura nelle scelte riproduttive - Fulvia D’Aloisio (EtnoAntropologia)
Economic aspects are generally considered as important variables in explaining the Italian low fertility rate: the cost of children – either direct or opportunity costs – heavily  influences reproductive choices. Furthermore, we have to take into account both the availability and the costs of family services, which consistently vary across the Italian regions. Literature on family in Italy has often highlighted the importance of kinship support networks, based on the spatial proximity of the family: such networks are effective both in integrating familiar economic resources and in coping with the deficiencies of welfare.